UTILIZATION OF CHICKEN INTESTINE AS AN ALTERNATIVE PROTEIN SOURCE IN THE DIET FOR FINGERLINGS OF CIRRHINUS MIRIGALA - A. B. Tabinda; R. Ghazala; A. Yasar; M. Ashraf (Journal of Animal and Plant Sciences, 2013)
Suitability of chicken intestine as an alternate protein source was evaluated for the diet of Cirrhinus mirigala fingerlings. Percentage protein, fat, ash, fiber, moisture and available energy (Kcal/100g) for the experimental diets were analyzed. Five experimental diets were formulated with chicken intestine meal 0% (FM100 Control), 25% (FM75), 50% (FM50), 75%(FM25) and 100% (FM0) substituting 0, 25, 50, 75, and 100% of the fish meal (FM) respectively. FM100 served as control diet. Experimental diets were iso-nitrogenous, iso-lipidic and iso-energic with 40% protein, 7.7-8.7% lipid and 425- 446kcal energy per 100g diet. Sixtey days feeding trial experiment was performed in static indoor conditions. FM75 had almost similar growth as compared to control (FM100) in Cirrhinus mirigala fingerlings diets. Significantly higher growth was recorded in FM50 as compared to FM100 (control) and FM75. Present study showed overall significantly higher growth in FM25 (P<0.01) and FM0 (P<0.05) as compared to the control. Lowest feed conversion ratio was observed in higher growth dietary treatments and vice versa. The results of the present study concluded that although best growth was achieved in the dietary treatment FM25 but without compromising growth 100% chicken intestine could be substituted for fish meal without addition of amino acids in Cirrhinus mirigala fingerlings diet.
Keywords: Carp fingerlings diet; Chicken intestine meal; Cirrhinus mirigala; fish meal replacement